MANAJEMEN PENDIDIKAN BERBASIS BUDAYA LOKAL LAMPUNG (Analisis Eksploratif Mencari Basis Filosofis) - Diana, Nirva (Universitas Islam Negeri Raden Intan Lampung, 2012)
Education is a tool to raise the degree and quality of the nation. Good management is needed to keep educational process continuing. Conventional management is going to silence the world of education in responding to the challenges of time and modernity. In the meantime, Lampung community still has a strongly local culture and it has great potential to become a major principle for the implementation of an ideal education. Management education based on local culture is, by itself, a manifestation of democratic education and community based (community-based education). By using methods of descriptive and phenomenological approach, it is understood that the culture of Lampung-based management of education is a necessity for management reform in education, particularly among the Lampongs. In addition, it also has a normative as well as the philosophical foundation rooted in the values of local traditions, as well as the demands of an increasingly democratic era and in the country with a democratic system.